2016
DOI: 10.1080/1612197x.2016.1256340
|View full text |Cite
|
Sign up to set email alerts
|

Being fit and feeling pleased: The mediational role of physical self-efficacy in UAE women residents

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Furthermore, exercising has been found to improve one's physical and mental abilities (Cantor & Bernay, 1992; Sebire, Standage, & Vansteenkiste, 2009). Such enhancing effect occurs through multiple processes, that is, an increase in the understanding of one's bodily potential (MacKinnon et al, 1987; Puente & Anshel, 2010), improvement of physical self‐perceptions (Salci & Ginis, 2017), development of self‐confidence (Talbot, 2001) and advancements in persistence and self‐efficacy (Dickerson & Taylor, 2000; Mosanya & Petkari, 2018; Puente & Anshel, 2010). Consequently, exercising can boost control over one's life (Boehm & Staples, 2004; Kwan, Caldwell Hooper, Magnan, & Bryan, 2011; Staples, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, exercising has been found to improve one's physical and mental abilities (Cantor & Bernay, 1992; Sebire, Standage, & Vansteenkiste, 2009). Such enhancing effect occurs through multiple processes, that is, an increase in the understanding of one's bodily potential (MacKinnon et al, 1987; Puente & Anshel, 2010), improvement of physical self‐perceptions (Salci & Ginis, 2017), development of self‐confidence (Talbot, 2001) and advancements in persistence and self‐efficacy (Dickerson & Taylor, 2000; Mosanya & Petkari, 2018; Puente & Anshel, 2010). Consequently, exercising can boost control over one's life (Boehm & Staples, 2004; Kwan, Caldwell Hooper, Magnan, & Bryan, 2011; Staples, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that exercising is correlated with physical self‐efficacy and that engagement in sports can be significantly enhanced through stimulation of physical self‐efficacy (Strauss, Rodzilsky, Burack, & Colin, 2001). Additionally, a study on women in the UAE revealed that the enhancing effect of exercising on mood is partially mediated by the changes in physical self‐efficacy (Mosanya & Petkari, 2018). On the other hand, exposure to certain cultural gender pressures and expectations may negatively predict women's self‐efficacy, which might be partially explained by the activation of gender‐related stereotypes (Kuchynka et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations